Peran Lembaga Pusat Pelaporan dan Analisis dalam Penaggulangan Tindak Pidana Money Laundring - I Wayan Panca Eka Darma; I Made Minggu Widyantara; Ni Made Sukaryati Karma (Warmadewa Press, 2020)
The duties, authorities, functions and criminal acts of money laundering in Indonesia are regulated in Law No. 8 of 2010 concerning the Prevention and Eradication of Criminal Acts of Money laundering. This study examines two issues: the role of the PPATK agency in combating money laundering after the enactment of Law No. 8 of 2010 concerning the Prevention and Eradication of Money laundering and criminal sanctions against perpetrators of criminal acts of money laundering in Indonesia. This research uses normative legal method, a process of finding legal rules, legal principles, and legal doctrines in order to answer the legal issues under study from the perspective of statutory regulations. PPATK is an independent agency that has 3 main roles in the prevention and eradication of money laundering, namely: receiving reports on suspicious financial transactions, analysing the reports received from reporting parties, and forwarding the results of report analysis to the authorised party. Article 2 paragraph 1 jo Article 18 of Law Number 31 of 1999 concerning Criminal Acts of Corruption as amended into Law Number 31 of 2001 concerning the Amendment to Law Number 31 of 1999 jo Article 55 paragraph 1 of the Criminal Code. Subsidiarily Article 3 jo Article 18 Law Number 31 of 1999 concerning Eradication of Corruption Crime as amended to Law Number 20 of 2001 concerning the Amendment to Law Number 31 of 1999 jo Article 55 paragraph 1 of the Criminal Code. Secondly, Article 3 paragraph (1) letter g of Law Number 25 of 2003 concerning the Amendment to Law Number 15 of 2002 concerning the Criminal Acts of Money laundering jo Article 55 paragraph (1) of the Criminal Code.